Sistemas alimentares para a recria de novilhas de corte - Amaral Neto, Luiz Gonzaga do (2020)
The objective was to evaluate productive and reproductive performance of beef heifers receiving 0.5% of balanced supplement, as well as the gross margin and direct financial return of the food systems during winter period and to evaluate productive performance, length of stay and number of bits in feeding station, as well as the displacement between each feeding station in heifers under continuous and rotational grazing in Papuã pasture during summer. Experiments were developed on Animal Science Department area at Federal University of Santa Maria. In winter, experimental area used corresponded to 6.4 hectares, divided into eight paddocks of 0.8 hectares each, which constituted the experimental units. Each paddock was divided into five 0.16 ha plots. Field evaluations were carried out from July 21 to November 3, 2016. The feeding systems consisted of beef heifers exclusively on ryegrass pasture (Lolium multiflorum Lam.) and on ryegrass pasture receiving 0.5% of balanced supplement. Forty Angus heifers were used with an initial average age of eight months and 159 ± 28 kg body weight, with three test heifers being allocated to each experimental unit. The grazing method used was rotational, with a variable number of animals and successive periods of occupation and rest. In the summer, experimental area corresponded to 4.8 hectares, with 6 subdivisions of approximately 0.8 hectares each, which constituted the experimental units. The treatments consisted of beef heifers under continuous or rotational grazing managements on Papuã, totalizing five grazing periods, where the first four lasted 16 days with four days of occupation in each plot and twelve days of rest and the last lasted for 24 days with six days of occupation, summing 88 days of use. Twenty-four Angus heifers were used, with an average initial age of 15 months and an initial average weight of 257 kg of body weight (BW), distributed in six paddocks, with four test heifers per paddock. The use of 0.5% balanced supplement promotes a substitutive and additive effect in a combined manner, allowing heifers to reach puberty early. The highest gross margin was seen in the food system using supplements and the best direct financial return in the system exclusively on pasture. The grazing method does not change the forage supply, nor does the leaf:stem ratio, changing the average daily gain. The stocking rate and weight gain per hectare were higher in rotational grazing method. The stay time between stations was not changed by grazing method, whereas steps between stations and number of bits per season were different between grazing methods.